2019
DOI: 10.1103/physrevfluids.4.084004
|View full text |Cite
|
Sign up to set email alerts
|

Viscous drag force model for dynamic Wilhelmy plate experiments

Abstract: In this work we revisit the dynamic Wilhelmy plate method for measuring dynamic contact angles with a specific focus on the viscous drag force which acts along the submerged surface of the plate. Particle image velocimetry shows that the viscous drag force can induce significant contact angle measurement errors if ignored. Preexisting models are found to underestimate the viscous drag force at moderate to high Capillary numbers, in finite-sized fluid domains, and for curved interfaces. Therefore, we propose a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…138,139 Furthermore, Zhang et al found that the viscous drag forces acting on the submerged plate surface during a dynamic Wilhelmy plate experiment could be of the same order of magnitude as surface tension forces, which were always highly underestimated due to the ignorance of the interface curvature, the tip of the plate, or the flow formed between the plate and liquid container. 140 They further proposed a new viscous drag force model that incorporated the effects of the moving contact line, the leading edge of a flat plate and a Couette–Poiseuille flow to measure CA by the Wilhelmy plate method, and the results of their demonstrative example showed that CA values of glycerin advancing on glass plate increased by 20° while the capillary number varied from 10 −3 to 10 −1 .…”
Section: Liquid-repellent Surfacesmentioning
confidence: 99%
“…138,139 Furthermore, Zhang et al found that the viscous drag forces acting on the submerged plate surface during a dynamic Wilhelmy plate experiment could be of the same order of magnitude as surface tension forces, which were always highly underestimated due to the ignorance of the interface curvature, the tip of the plate, or the flow formed between the plate and liquid container. 140 They further proposed a new viscous drag force model that incorporated the effects of the moving contact line, the leading edge of a flat plate and a Couette–Poiseuille flow to measure CA by the Wilhelmy plate method, and the results of their demonstrative example showed that CA values of glycerin advancing on glass plate increased by 20° while the capillary number varied from 10 −3 to 10 −1 .…”
Section: Liquid-repellent Surfacesmentioning
confidence: 99%
“…The use of fiber instead of a plate gives considerable advantages. For example, steady-state measurements are possible with high viscosity liquids, which is a challenge at present [23]. The meniscus height rapidly settles at equilibrium on small diameter and stationary fiber, resulting in high accuracy of results [24].…”
Section: Introductionmentioning
confidence: 99%